Demystifying disinformation shadow economies: fake news work models in Indonesia and the Philippines. Issue 3 (4th May 2022) - Ong, Jonathan Corpus; Tapsell, Ross
ABSTRACT: Engaging with the special issue theme of media freedom 'from below, ' this article contributes ethnographically grounded and comparative research of two democratic Southeast Asian countries dealing with urgent threats to media freedom and democracy: Indonesia and the Philippines. Our research identifies the main disinformation work models in Southeast Asia, most notably through the use of buzzers (Indonesia) and trolls (the Philippines). Our research examines the increasingly gray area between trolls, buzzers and disinformation, and their increasing relationship to political elites. By explaining recent practices of political disinformation campaigns and journalist harassment, we aim to deepen understanding as to how these campaigns are organized in order to prevent them in the future. This article ultimately calls for a critical collaboration with diverse stakeholders in countering 'fake news' by examining four dominant disinformation work models.